Assessment of digestates prepared from maize, legumes, and their mixed culture as soil amendments: Effects on plant biomass and soil properties - Hammerschmiedt, Tereza; Kintl, Antonín; Holatko, Jiri; Mustafa, Adnan; Vitez, Tomas; Malicek, Ondrej; Baltazar, Tivadar; Elbl, Jakub; Brtnicky, Martin (Frontiers in Plant Science, 2022)
Digestate prepared from anaerobic digestion may serve as a fertilizer as it contains ample amounts of plant-available nutrients, mainly of nitrogen, phosphorous and potassium. Digestates produced from mixed intercropped cereal and legume biomass has a potential to enrich soil and plants with nutrients more efficiently than monoculture-based digestates. The objective of this study was to determine the impact of different types of digestates applied at the rate (40 tha-1 of liquid matter) on the soil properties and crop yield in a pot experiment with lettuce (Lactuca sativa). Anaerobic digestion of silages prepared from following monocultures and mixed cultures: Broad bean, Maize, Maize + Broad bean, Maize + White sweet clover and White sweet clover, was performed in an automatic custom-made system and applied to the soil Results revealed that, fresh and dry above ground biomass was significantly increased in all digestate-amended variants in comparison to the control. The demonstrably highest content of total nitrogen and urease (indicator of nitrification), oxidizable carbon was observed for Maize digestate amendment. Broad bean digestate mediated the highest phosphatase activity, basal respiration and N-acetyl--D-glucosamine, L-alanine and L-lysine induced respiration. Maize + Broad bean digestate resulted the highest values of N-acetyl-β -D-glucosaminidase and -glucosidase, Maize + White sweet clover digestate revealed the highest value of arylsulfatase. We ascribe these observed differences to the effect of increased soil degradability of legume digestate derived organic matter and joint increased availability of nutrients after application.